Currículo surdo no ensino de ciências para quem fala com as mãos e ouve com os olhos - Vale, Jackson da Silva (2021)
This dissertation has as general objective to know the articulations between school curriculum, learning of the Deaf and the Deaf student, weaving dialogues between these conceptions, analyzing the school curriculum as science teaching to Deaf students and presenting a proposal for a disciplinary deaf curriculum for those who speak with their hands and listen with their eyes. The following specific objectives unfold from it: 1) systematize conceptions about the school curriculum, learning of the Deaf and the Deaf student; 2) analyze the disciplinary school curriculum as science teaching to Deaf students and 3) present a proposal for a curriculum as science teaching related to Mathematics, for the 5th year of elementary school, from Deaf to Deaf. In the theoretical foundation I use authors such as Silva (1996, 1999 and 2013); Young (2014); Perlin (1998); Tables (1997); Lourenço (2017) and Campello (2008). Just as I base myself on the concepts of Vygotski's Historical-Cultural Theory (1997). In the methodological procedures I bring the dialectical method of Gamboa (2007). This research is bibliographical and documentary in nature. I consulted documents such as the Common National Curriculum Base - BNCC, the National Curriculum Parameters - PCNs, the Common National Curriculum Base in Amazonas and the Curriculum Guidelines for National Education. The research results indicate that despite all the advances in Deaf education, the school curriculum still does not include the educational specificities of the Deaf, which devalues sign language and deaf culture. Furthermore, I identified that the use of Sign Language as a language of instruction, classifiers and hands are fundamental for the teaching of students with deafness. The research findings indicate that a Deaf curriculum is needed in Deaf children's schools for a better acquisition of school content and, consequently, a higher quality in the human development of children with deafness. Finally, this work contributes to the construction of the education of those who speak with their hands and listen with their eyes. This deaf curriculum was intended to provide more efficient learning for deaf students. Keywords: School Curriculum. Deaf Culture. Deaf Curriculum.